Mapping gastrointestinal gene expression patterns in wild primates and humans via fecal RNA-seq - Sharma, Ashok Kumar; Pafčo, Barbora; Vlčková, Klára; Červená, Barbora; Kreisinger, Jakub; Davison, Samuel; Beeri, Karen; Fuh, Terence; Leigh, Steven R.; Burns, Michael B.; Blekhman, Ran; Petrželková, Klára J.; et al. (BMC genomics, 2019)
Background Limited accessibility to intestinal epithelial tissue in wild animals and humans makes it challenging to study patterns of intestinal gene regulation, and hence to monitor physiological status and health in field conditions. To explore solutions to this limitation, we have used a noninvasive approach via fecal RNA-seq, for the quantification of gene expression markers in gastrointestinal cells of free-range primates and a forager human population. Thus, a combination of poly(A) mRNA enrichment and rRNA depletion methods was used in tandem with RNA-seq to quantify and compare gastrointestinal gene expression patterns in fecal samples of wild Gorilla gorilla gorilla ( n = 9) and BaAka hunter-gatherers ( n = 10) from The Dzanga Sangha Protected Areas, Central African Republic. Results Although only a small fraction (< 4.9%) of intestinal mRNA signals was recovered, the data was sufficient to detect significant functional differences between gorillas and humans, at the gene and pathway levels. These intestinal gene expression differences were specifically associated with metabolic and immune functions. Additionally, non-host RNA-seq reads were used to gain preliminary insights on the subjects’ dietary habits, intestinal microbiomes, and infection prevalence, via identification of fungi, nematode, arthropod and plant RNA. Conclusions Overall, the results suggest that fecal RNA-seq, targeting gastrointestinal epithelial cells can be used to evaluate primate intestinal physiology and gut gene regulation, in samples obtained in challenging conditions in situ. The approach used herein may be useful to obtain information on primate intestinal health, while revealing preliminary insights into foraging ecology, microbiome, and diet.